Laporan Kasus: Kegoyangan Gigi Pada Pasien disertai Diabetes Mellitus - Pascalis Adhi Kurniawan; Rinawati Satrio (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2020)
Diabetes Mellitus is a metabolic disorder characterized by an increase in blood glucose levels (hyperglycemia) due to disturbances in insulin secretion and insulin action. Diabetes mellitus (DM) is a disease characterized by high blood glucose levels, because the body cannot release or use insulin adequately. There are many factors that trigger or aggravate periodontitis, including plaque accumulation, calculus (tartar), and systemic factors such as diabetes mellitus. Objective: To explain that there is a close relationship between elevated blood glucose levels and periodontitis. Case Description: A 77 year old woman presented with a loose left upper tooth and pain during eating. The patient admitted to having a history of systemic disease, namely diabetes mellitus. Intra oral examination was found on 27th grade 3 luxation, 6 mm gingival recession, 4 mm probing depth, debris around the teeth, oral hygiene tends to be poor. The therapy provided is in the form of education on the effect of diabetes mellitus on teeth and the condition of the oral cavity in general, as well as the importance of maintaining health and food consumption so that blood sugar conditions are controlled. Conclusion: Periodontal disease can be affected by DM. Periodontitis is one of the manifestations of DM in the oral cavity. The severity of periodontitis can result from an increase in blood glucose levels.